2017
DOI: 10.1007/s11139-017-9891-8
|View full text |Cite
|
Sign up to set email alerts
|

Determining Hilbert modular forms by central values of Rankin–Selberg convolutions: the weight aspect

Abstract: The purpose of this paper is to prove that a primitive Hilbert cusp form g is uniquely determined by the central values of the Rankin-Selberg L-functions L(f ⊗ g, 12 ), where f runs through all primitive Hilbert cusp forms of weight k for infinitely many weight vectors k. This result is a generalization of the work of Ganguly, Hoffstein, and Sengupta [3] to the setting of totally real number fields, and it is a weight aspect analogue of the authors own work [6].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…More precisely, let g ∈ Π l (n) for some fixed l ∈ 2N n and n ⊂ O F . By obtaining an asymptotic formula for the harmonic sum of the values L( 1 2 , f ⊗ g) as f varies in Π k (O F ) (which the authors showed in [11,Proposition 2.4]) and using the subconvexity bound L(…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, let g ∈ Π l (n) for some fixed l ∈ 2N n and n ⊂ O F . By obtaining an asymptotic formula for the harmonic sum of the values L( 1 2 , f ⊗ g) as f varies in Π k (O F ) (which the authors showed in [11,Proposition 2.4]) and using the subconvexity bound L(…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the second moment of Rankin-Selberg L-functions, the Voronoi summation formula is based on the class number one assumption. Thus, for a real number field with arbitrary class number a new version of this has to be proven, a Kloosterman sum for totally real number fields of arbitrary class number is given in [HT16].…”
Section: Discussionmentioning
confidence: 99%
“…Any f ∈ S k (c) has a Fourier expansion We will consider a subspace of the cusp forms, the so called newforms S k (c). This space is defined as the orthogonal complement with respect to the inner product of the oldforms where the oldforms S k (c) are the cusp forms coming from lower level, see [HT16,page 4].…”
Section: Hilbert Modular Formsmentioning
confidence: 99%
See 2 more Smart Citations